2016
DOI: 10.17221/127/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Improving agricultural performance for the working poverty reduction in the European Union

Abstract: Th e main objective of the paper is to highlight the impact of agricultural performance on working poverty in the EU countries, in the 2008-2013 period, for identifying some measures that need to be taken to increase the agricultural performance so that the in-work poverty reduces. Th e comparative analysis shows that agricultural performance, according to the agricultural indicators analysed and the phenomenon of working poverty vary signifi cantly across the EU countries. Th e correlation and regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…While these results are not surprising, this research provides original findings based on regression models: working in agriculture implies, all else being equal , a higher risk of being poor when the relative poverty line is set at 60 per cent or even at 50 per cent of median income. This is similar to Herman’s () result showing that for the EU working poverty is positively linked with working in agriculture as self‐employed, salaried or unpaid family workers.…”
Section: Discussionsupporting
confidence: 89%
“…While these results are not surprising, this research provides original findings based on regression models: working in agriculture implies, all else being equal , a higher risk of being poor when the relative poverty line is set at 60 per cent or even at 50 per cent of median income. This is similar to Herman’s () result showing that for the EU working poverty is positively linked with working in agriculture as self‐employed, salaried or unpaid family workers.…”
Section: Discussionsupporting
confidence: 89%
“…Corroborating these results with the positive link between vulnerable employment and employment in agriculture (r = 0.644, p < 0.01), it is shown that, in EU countries, during the 2007-2016 period, vulnerable workers, mainly those who work in agriculture, suffered the consequences of working poverty risk. Moreover, this implies that both agricultural productivity and the income for agricultural workers need to increase to reduce working poverty [44]. In order to test Hypothesis H5, we took into consideration the cumulative influence of 14 socio-economic variables selected, the inclusive and sustainable development indicators, productive employment indicators, and indicators which reflect the deficit in productive employment and poverty (see Table 1), employing complex statistical methods of data analysis, principal component analysis (PCA), and cluster analysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The countries that manage to increase productivity and pull out of poverty are those that were able to diversify away from agriculture and other traditional sectors [16,28,38]. A strong negative correlation between economic development (GDP per capita) and shares of agriculture in GDP [9] and in employment [44] were found, which can be explained by the significant contribution of agriculture to employment, in countries with low economic development. A real challenge facing employment in agriculture is its low quality due to the low productivity in traditional activities [9,44].…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations